Formation features of the parameters of the model winter bread wheat variety of intensive type for the conditions of the Rostov region - S. N. Gromova; O. V. Skripka; S. V. Podgorny; A. P. Samofalov; V. L. Chernova (Зерновое хозяйство России, 2021)
Breeding success is determined by the correct choice of agro-ecotype. In this regard, we have carried out a comprehensive estimation of 75 winter bread wheat varieties and samples of the competitive trials. The variety ‘Ermak’ was used as a standard. The study was carried out using the material and technical base of the Federal State Budgetary Scientific Institution Agricultural Research Center “Donskoy” (FSBSI “ARC “Donskoy”) in 2017–2019. The purpose was to study the correlation among economically valuable traits of winter bread wheat varieties and samples and to find genotypes similar in their parameters to the model variety based on curvilinear regressions. As a result of the phenotypic estimation of the quantitative traits of winter bread wheat varieties and samples, there was determined an average level and their variability degree. Their productivity ranged from 8.52 to 10.51 t/ha. Through the years of study, the variation coefficients indicated a high stability of these features (from 0.9 to 10.0%). In order to identify the similarities and differences between varieties and samples, there has been conducted a cluster analysis. As a result of this analysis, there has been selected the winter bread wheat variety ‘Yubiley Dona’ (C25), parameters which were more identical to the model (C76). This variety is recommended for further breeding process to improve the studied basic economic traits.